Using the International Standard of Auditing 315 “Identifying and Assessing the Risks of Material Misstatement through Understanding the Entity and Its Environment” in the Auditing Practice - O. LUBENCHENKO; M. KORINKO (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2021)
The article contains results of a study focused on practical issues of the application of the International Standard of Auditing (ISA) 315 “Identifying and Assessing the Risks of Material Misstatement through Understanding the Entity and Its Environment”. It is argued that by using provisions of ISA 315 at the phase of planning of an auditing engagement, managers of an auditing entity have to assess sectoral, regulatory and other external factors with impact on the financial reporting process, including the involved conceptual framework. The characteristics of an auditing entity to be analyzed by the auditor are determined: nature of business, pattern of ownership and corporate management, types of investment, structure and methods of financing. The auditor’s analysis of these issues has to result in his/her conclusion about the inherent risk, which is the risk of client’s business. When planning audit for small firms, an auditor can make use of the so called economies of scales. It means that small firms can minimize the measures of control through introducing components of the control environment in a way different from other business entities classified as large by activity scopes. Auditing procedures pertaining to components of the control environment should be initiated through inquiries, observations, reviews of documents and/or risk assessment procedures. A systematization of business risks and measures of control over audit customers, conditions and events that may signal the existence of risks of significant material misstatement in financial statements is made.